KELAYAKAN INVESTASI KREMATORIUM SANTHA GRAHA TUNON DESA ADAT BEDHA KABUPATEN TABANAN - I Nengah Subagia; I Gusti Agung Ayu Istri Lestari; I Wayan Sony Mahayasa (Program Studi Teknik Sipil Fakultas Teknik Universitas Mahasaraswati Denpasar, 2021)
Ngaben ceremony is included in Pitra Yadnya ceremony. Pitra Yadnya is a sacred offering or sacrifice shown to the ancestors sincerely based on the payment of debts to parents or ancestors. The customary system that has not been able to be carried out to the maximum, especially the people who are busy working, the community uses pitra yadnya ceremony at the Crematorium. The establishment of crematorium in Bedha Traditional Village named Santha Graha Crematorium is accommodating crematorium place that does not exist in West Bali area. The purpose of this research is to find out the investment feasibility of Santha Graha Tunon Crematorium Desa Adat Bedha is feasible or not from the financial aspect. The data collection technique in this analysis is to visit the location of Santha Graha Crematorium in Bedha Traditional Village, meet with the Chief Manager of Santha Graha Desa Adat Bedha Crematorium and staff to obtain the necessary data such as cost capital, crematorium service rates, ambulance rates, banten (upakara) tariffs, operational costs, and maintenance costs. Investment feasibility analysis reviewed in the form of financial aspects with NPV, IRR, Net B/C and Payback Period analysis. In the research at The Crematorium Santha Graha Tunon Desa Adat Bedha obtained the results of net present value (NPV) investment criteria of Rp. 12,627,720,181.95 > 0, Internal Rate of Return (IRR) 51.66 % > 16.8 % Net B/C 5.97 > 1, Payback period (PBP) within 3 years 2 months < 15 years. Of the four methods of investment criteria in the Crematorium Santha Graha Tunon Desa Adat Bedha is declared very feasible to be implemented because all are already eligible.